Unsettling Environmentalism: Decolonial Musings - Zachariah, George (International review of mission, 2024)
Decolonial ecological imaginations entail a critical interrogation of mainstream environmentalism to unmask and unsettle it. These reflections expose how mainstream environmentalism legitimizes and perpetuates the colonization of the Earth and subaltern and Indigenous communities. Mainstream environmentalism is a colonial project to perpetuate the interests of settler colonialism and racial capitalism. This calls for a new search for decolonial and alternative ecological reimagination, informed by the epistemologies and eco-politics of the Indigenous and subaltern communities and other grassroots social movements. Decolonial ecological imaginations involve the task of contesting and unsettling settler colonialism, extractive/exploitative capitalism, white supremacy, and all ideologies and practices of domination and exclusion.